Gender and Traditional Music Performance in Yoruba Land - Ogunyemi, Bayo (Journal of Gender and Power, 2024)
This paper discusses gender as a social reality from the perspective of the Yoruba people of South west, Nigeria. The paper hypothesizes that, the composition of Yoruba musical ensembles and the people’s musical activities, replicate their worldview of gender. Therefore, portray of Yoruba as a patriarchy society may not be adequate in representing the people’s view of the gender concept. The paper employs the practices and conventions in Yoruba traditional music ensembles to navigate the entire gamut of the discourse. Using ethnographic approach, data for the paper were collated from the six Yoruba states of Nigeria using mixed methods of interview, observation and bibliography. It hinges on the theory of gender complementarities, by Olajubu, 2003), the paper establishes the relativity of gender in Yoruba land. Though the Yoruba cultures is gender sensitive, the people, by their practices, see each of the sexes as complimenting the other and not subordinate or subservient. Therefore, sex to the Yoruba people is an expression of human physiology beyond an object for social stratification.